Philippine Health Insurance Corporation a total systems study - Javier, Brendalyn C.; Jogno, Jayson M.; Reynoso, Gemelyn M.; Sabellano, Ces B.
This report describes an initial attempt to explore the development of Information System Insfrastructure for Philippine Health Insurance Corporation (PHIC) to support the identification, collection and analysis of major health data necessary for the implementation of Universal Helth Care. To achieve this goal, the project is specifically concentrated on the Membership segment PHIC Network wherein a rich source of data is mined for health management. The methodology is anchored on the objectives of a (a) identification of internal and partner data requirements of PHIC, (b) determination of information level of access of partners and stakeholders of PHIC and (c) design of conceptual Data Architecture of a new Integrated PHIC Membership Information System backed up by Standard terminologies. The proposed solution consists of an integrated PHIC information network module that is based on the concepts of cloud computing so the information sharing and high-end processing is available in the "cloud" resulting to scalble and greater computing efficiency while addressing privacy and security concerns in information sharing. Such a system would also empower all members with the automated ownership of their secure personal and medical records while its interface can be extended to provide an anonymous view for all medical records for research purposes to scientified community and organizations such as Department of Health and clinical research centers.